2018
DOI: 10.1111/echo.13869
|View full text |Cite
|
Sign up to set email alerts
|

A late presentation of congenital cardiac anomaly: Accessory chordae from the left atrium causing severe mitral regurgitation

Abstract: Mitral regurgitation secondary to accessory mitral valve (MV) chordae of the left atrium is an extremely rare congenital disease. A 85-year-old female (NYHA I-II) was hospitalized for investigations. An echocardiogram showed calcification of the MV with mild stenosis and moderate regurgitation. Transesophageal three-dimensional echocardiogram revealed a band-like structure extending from the distal third of the anterior wall of the left atrium to the MV. This accessory chordae determined severe systolic regurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…4 Left atrial mitral valve chordae have been identified in children as young as 8-years-old, 12 while one case was only diagnosed at the age of 85-years-old. 6 At 59-years-old, our patient was asymptomatic from his valvular pathology and his finding was incidental. It has been hypothesised that symptoms may be delayed by progressive growth and dilatation of the left atrium, resulting in gradual traction of the aberrant chord eventually resulting in leaflet prolapse.…”
Section: Case Reportmentioning
confidence: 73%
See 3 more Smart Citations
“…4 Left atrial mitral valve chordae have been identified in children as young as 8-years-old, 12 while one case was only diagnosed at the age of 85-years-old. 6 At 59-years-old, our patient was asymptomatic from his valvular pathology and his finding was incidental. It has been hypothesised that symptoms may be delayed by progressive growth and dilatation of the left atrium, resulting in gradual traction of the aberrant chord eventually resulting in leaflet prolapse.…”
Section: Case Reportmentioning
confidence: 73%
“…The origin of left atrial mitral valve chordae is proposed to be a result of a developmental defect during embryogenesis between the 14th and 17th weeks of gestation as the papillary muscles and chordae develop 4 . Left atrial mitral valve chordae have been identified in children as young as 8‐years‐old, 12 while one case was only diagnosed at the age of 85‐years‐old 6 . At 59‐years‐old, our patient was asymptomatic from his valvular pathology and his finding was incidental.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence in the population is largely unknown, and the clinical relevance is unclear. A number of case reports highlight anomalous left atrial chords as a cause of significant mitral regurgitation for which surgical treatment can be indicated ( 1 ). In addition, there is 1 report of a left atrial chord being involved in a complex endocarditis case ( 2 ).…”
mentioning
confidence: 99%